2013
DOI: 10.1509/jmr.11.0394
|View full text |Cite
|
Sign up to set email alerts
|

The Hesitant Hai Gui: Return-Migration Preferences of U.S.-Educated Chinese Scientists and Engineers

Abstract: Managers, research administrators, and policy makers need a greater understanding of the factors that drive employment preferences of foreign science, technology, engineering, and mathematics (STEM) doctoral graduates of U.S. universities. To address this need, the authors report the results of a large multischool conjoint survey of return-migration preferences among U.S. STEM doctoral students from China. The survey presents the respondents with potential job offers and yields individual-level estimates of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This study has important implications for global academic mobility, because Chinese citizens not only account for a large share of the US and EU STEM PhD graduates but also are among the most productive graduates ( 5 ). As China continues to invest in higher education and academic talent, we can expect more Western-trained Chinese students to return to China, although findings were mixed; whereas a National Science Foundation survey showed that 87% of Chinese STEM PhDs wanted to stay in the US ( 15 ), another study revealed that 70% of them would prefer to return to China if offered salaries comparable to what they could expect to receive in the US ( 17 ). We can also expect Chinese universities to become more attractive locations for Chinese (and international) students intending to pursue scientific research careers—students who would otherwise study in the US or EU.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…This study has important implications for global academic mobility, because Chinese citizens not only account for a large share of the US and EU STEM PhD graduates but also are among the most productive graduates ( 5 ). As China continues to invest in higher education and academic talent, we can expect more Western-trained Chinese students to return to China, although findings were mixed; whereas a National Science Foundation survey showed that 87% of Chinese STEM PhDs wanted to stay in the US ( 15 ), another study revealed that 70% of them would prefer to return to China if offered salaries comparable to what they could expect to receive in the US ( 17 ). We can also expect Chinese universities to become more attractive locations for Chinese (and international) students intending to pursue scientific research careers—students who would otherwise study in the US or EU.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…As observed globally, the academic labour market appeared to be closely related to public funding for Higher Education (HE) sectors. In the 2000s, major countries in both West (Passaretta et al, 2019;Zeithammer & Kellogg, 2013) and East Asia (Shin et al, 2018;Yoshioka-Kobayashi & Shibayama, 2021) experienced dramatic decreases in academic professions (hereafter APs and NAPs for non-academic professions) availability. This decline was accompanied by an increase in fixed-term contracts as a result of the radical HE reforms catalysed by the 2008 economic recession and the concurrent expansion of doctoral education.…”
Section: Labour Market Conditions: Within Academiamentioning
confidence: 99%
“…These geographic disparities in NAP provision could result in frequent occupational mobility among doctorates, who tended to migrate towards locales with more R&D investments and greater employment availability (Passaretta et al, 2019). Thus, it came as no surprise that regions with intensified R&D investment-like Northwestern European countries (Reale et al, 2019) and the US (Sinche et al, 2017;Zeithammer & Kellogg, 2013)seemed to experience a net gain in global brain circulation. However, the presence of children and older age when obtaining doctoral degrees (Reale et al, 2019), as well as visa policy (Jackson & Michelson, 2015;Roach & Skrentny, 2019;Zeithammer & Kellogg, 2013) occasionally hindered such mobility.…”
Section: Labour Market Conditions: Beyond Academiamentioning
confidence: 99%
“…As China's middle class grows, more and more people can afford and choose to self-fund their studies abroad (Machin & Murphy, 2017). These previous works have investigated more about Asian students' acculturation processes (Brisset et al, 2010;Yu et al, 2019;, employment preferences (Zeithammer & Kellogg, 2013), and effects on scientific productivity at their destinations (Borjas et al, 2018;Gaulé & Piacentini, 2013). A few articles have examined students from Africa, the US, and European countries, but they appear to be underrepresented.…”
Section: Contextsmentioning
confidence: 99%